Analisis Peran Badan Permusyawaratan Desa (BPD) Dalam Penyelenggaraan Pemerintahan Di Desa Pao Kecamatan Tombolopao Kabupaten Gowa - St. Ainun Mardiyah; Nurlinah Nurlinah (Departemen Ilmu Pemerintahan Fisip Unhas, 2019)
This study aims to analyze the role of the Village Consultative Body (BPD) in the administration of governance in Pao Village, Buttonopao District, Gowa Regency and the factors that influence it, to achieve these objectives, qualitative research methods are used using descriptive data. Data collection techniques are used by means of observation, interviews, and documents and archives using qualitative descriptive analysis techniques. The results showed: First, Analysis of the Role of the Village Consultative Body (BPD) in Government Administration in Pao Village, Buttonopao Subdistrict, Gowa Regency, included Discussing and agreeing on village draft regulations with the village head where coordination is always carried out by the village government in this case the village head and parties BPD in the process of discussion and drafting village regulations so that it runs well in the process, Then from Accommodating and channeling the aspirations of the community, the role of BPD in this case as a reservoir of community aspirations has been carried out properly as expected.